2014
DOI: 10.1073/pnas.1405698111
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flows created by swimming bacteria drive self-organization in confined suspensions

Abstract: Concentrated suspensions of swimming microorganisms and other forms of active matter are known to display complex, self-organized spatiotemporal patterns on scales that are large compared with those of the individual motile units. Despite intensive experimental and theoretical study, it has remained unclear the extent to which the hydrodynamic flows generated by swimming cells, rather than purely steric interactions between them, drive the self-organization. Here we use the recent discovery of a spiral-vortex … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
332
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 371 publications
(348 citation statements)
references
References 49 publications
15
332
1
Order By: Relevance
“…In contrast to the classical second-order NS equations, the sixth-order PDE (3a) requires additional higher-order boundary conditions to specify solutions. Active components in a fluid can form complex boundary-layer structures [11][12][13], which are poorly understood experimentally and theoretically. To identify physically acceptable boundary conditions, we tested different types of higher-order conditions.…”
Section: Simulationsmentioning
confidence: 99%
“…In contrast to the classical second-order NS equations, the sixth-order PDE (3a) requires additional higher-order boundary conditions to specify solutions. Active components in a fluid can form complex boundary-layer structures [11][12][13], which are poorly understood experimentally and theoretically. To identify physically acceptable boundary conditions, we tested different types of higher-order conditions.…”
Section: Simulationsmentioning
confidence: 99%
“…In addition to the predicted global behaviour, this experiment had a surprising and unanticipated feature: a counter-rotating boundary layer at the drop periphery ('edge current'), perhaps one or two cells wide. It was initially unclear the direction in which the cells were swimming in this layer, relative to the bulk, but numerical studies (Lushi, Wioland & Goldstein 2014) suggested the counterintuitive result that the cells within the bulk vortex actually swim upstream against the 'backwash' from the boundary layer. This prediction was verified by use of a two-colour fluorescent labelling technique that allows one to visualise the cell body separately from the flagella, and thereby arrive at an unambiguous determination of the cell orientations in the domain.…”
Section: Collective Behaviour In Microswimmer Suspensionsmentioning
confidence: 99%
“…Extracellular polymeric substances (EPSs) play an important role in determining the structural and mechanical architecture of a biofilm (7)(8)(9)(10)(11)(12). Generally, the collective dynamics of bacterial colony involves a complex interplay of various physical, chemical, and biological mechanisms, such as growth and differentiation of cells, production of EPSs, the collective movement of cells determined by interacting physical forces and chemical cues, e.g., chemotaxis, motility, cellcell signaling, adhesion, and gene regulation (13)(14)(15)(16)(17)(18)(19). At low density, communication among cells occurs mainly through chemical signals (20).…”
mentioning
confidence: 99%